Menuju gereja sebagai komunitas pembelajar: Rekonstruksi teologi pendidikan agama Kristen berbasis spiritualitas partisipatif - Haposan Simanjuntak (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2025)
This study arises from a theological concern that Christian Religious Education (CRE) has been reduced to doctrinal transmission, thereby neglecting the dialectical dimension of faith formation. The prevailing instructive-hierarchical paradigm has produced congregations that are cognitively informed yet fail to mature into hermeneutical communities capable of collectively interpreting faith. This research aims to reconstruct the theological foundations of CRE through the framework of participatory spirituality. Employing a qualitative approach grounded in systematic literature review and a reflective-analytical approach to pastoral theology, faith pedagogy, and ecclesiological praxis, this study argues that participatory spirituality enables CRE to be reconceived as a dialogical, interactive, and transformative process of faith formation. The church is repositioned as a learning community wherein liturgy, ministry, and fellowship constitute the locus of formative encounter. In conclusion, this reconstruction offers an ecclesiological reorientation affirming the church's nature as the Body of Christ, growing through a relational learning ecology that culti-vates reflective, participatory, and contextual faith. Abstrak Penelitian ini berangkat dari kegelisahan teologis atas reduksi Pendidikan Agama Kristen (PAK) sebagai transmisi doktrinal yang mengabaikan dimensi dialektis pembentukan iman. Paradigma instruktif-hierarkis telah melahirkan jemaat yang terinformasi secara kognitif, namun tidak bertumbuh sebagai komunitas hermeneutis yang menafsirkan iman secara kolektif. Penelitian ini bertujuan merekonstruksi landasan teologis PAK melalui kerangka spiritualitas partisipatif. Dengan pendekatan kualitatif berbasis studi literatur sistematis dan pendekatan reflektif-analitis terhadap literatur teologi pastoral, pedagogi iman, serta praksis eklesiologis, penelitian ini merumuskan bahwa spiritualitas partisipatif memungkinkan PAK dipahami sebagai proses formasi iman yang dialogis, interaktif, dan transformatif. Gereja diposisikan sebagai learning community di mana liturgi, pelayanan, dan persekutuan menjadi locus pembentukan iman. Kesimpulannya, rekonstruksi ini menawarkan reorientasi eklesiologis yang menegaskan hakikat gereja sebagai Tubuh Kristus yang bertumbuh melalui ekologi pembelajaran relasional, membentuk iman yang reflektif, partisipatif, dan kontekstual.